Immunotherapy for Acute Myeloid Leukemia: Allogeneic hematopoietic cell transplantation is here to stay. (January 2022) - Kaleka, Guneet; Schiller, Gary
Highlights: Hematopoietic Stem Cell Transplant remains the only curative therapy for acute myeloid leukemia. Immunotherapy in AML is limited by therapy-associated toxicities, the lack of target antigens, and mixed success with existing agents. The use of immunotherapy in AML may be most effective when combined with chemotherapy as a bridge to stem cell transplant. Abstract: Acute Myeloid Leukemia (AML) represents 1 % of all new cancer diagnosis made annually in the US and has a five-year survival of 30 %. Traditional treatment includes aggressive induction therapy followed by consolidation therapy that may include a hematopoietic stem cell transplant (HSCT). Thus far, HSCT remains the only potentially curative therapy for many patients with AML owing to the graft-versus-leukemia effect elicited by this treatment. The use of novel therapies, specifically immunotherapy, in the treatment of AML has been limited by the lack of appropriate target antigens, therapy associated toxicities and variable success with treatment. Antigenic variability on leukemia cells and the sharing of antigens by malignant and non-malignant cells makes the identification of appropriate antigens problematic. While studies with immunotherapeutic agents are underway, prior investigations have demonstrated a mixed response with some studies prematurely discontinued due to associated toxicities. This review presents a discussion of the envisioned role of immunotherapy in the treatment of AML in the setting of mixed therapeutic success and potentially lethal toxicities.